Lower respiratory tract and plasma SARS-CoV-2 RNA load in critically ill adult COVID-19 patients: Relationship with biomarkers of disease severity. Issue 3 (September 2021) - Olea, Beatriz; Albert, Eliseo; Torres, Ignacio; Gozalbo-Rovira, Roberto; Carbonell, Nieves; Ferreres, José; Poujois, Sandrine; Costa, Rosa; Colomina, Javier; Rodríguez, Jesús; Blasco, María Luisa; Navarro, David
Highlights: SARS-CoV-2 RNA cleared at a faster in tracheal aspirates than in plasma. SARS-CoV-2 RNA load in plasma and tracheal aspirates correlated significantly. SARS-CoV-2 RNA load in tracheal aspirates and plasma correlated with serum levels of ferritin and LDH. A trend towards a higher mortality was seen in patients with SARS-CoV-2 RNAemia